Taurine 10 - Lee, Dong-Hee; Schaffer, S. W.; Park, Eunkyue; Kim, Ha Won (Springer, 2017)
This volume provides the reader with an overview of taurine and its derivatives in modulating brain health. One of the highlights of this book is that taurine helps in the recovery of Alzheimer model mice from cognitive deficits by directly binding to oligomeric?-amyloid. In addition, this book includes very intriguing results from a study that looks into the effects of taurine-carbohydrate derivatives in stimulating fibrillogenesis of amyloid-b and in reducing Alzheimer-like behaviors. This book also highlights several new roles for taurine, including its novel effects on the various body structures encompassing the central nervous system, the cardiovascular system, the immune system, and the endocrine system, along with a role for taurine complements in nutrition. This edited book contains original articles and reviews based on oral and poster presentations at the 20th International Taurine Meeting held in Seoul, Korea in May 2016. The theme of this conference was 'Taurine and Brain Health'. This volume will be relevant to anyone with an interest in the biological roles of taurine, from clinicians to nutritionists and from individuals working in the pharmaceutical industry to those working in food manufacturing.
Keywords: Taurine -- Congresses.; elektronické knihy; electronic books